PENGARUH LAMA PERENDAMAN PANGKAL SETEK DALAM LARUTAN NAA (NAPTHALENE ACETIC ACID) PADA PERTUMBUHAN SETEK LADA - Syaicha Fachrun Nisa; Niar Nurmauli; Akari Edy; Sugiatno Sugiatno (Jurnal Agrotek Tropika, 2020)
Effect of soaking duration on base stem cuttings in NAA solution (Naphthalene Acetic Acid) on the growth of pepper The need for pepper is increasing along with the development of the food industry with the basic ingredients of pepper. The determining factor of the quality of pepper produced comes from the seeds used. This study aims to determine the effect of soaking DURATION on pepper cuttings (Piper nigrum L.) in the Napthaleneacetic Acid (NAA) solution. The study was conducted in October 2018 until February 2019 in the greenhouse and Plant Science Laboratory of the Faculty of Agriculture, University of Lampung, Bandar Lampung. This study uses a completely randomized group design (RKTS). The treatment of immersion base cuttings in NAA (N) solution concentrates 500 ppm consisting of : without NAA (n0), immersion 0 minutes (n1), soaked 15 minutes (n2), soaked 30 minutes (n3), soaked 60 minutes (n4), and soaked 120 minutes (n5). Homogeneity of variability between treatments was tested by Bartlet Test and data additivity was tested by Tukey test, then continued with Variance Analysis (ANARA). Comparison of the middle value with the orthogonal comparison test at α level of 5%. The results showed that: (1) giving NAA affected the number of roots in the book, the fresh weight of the roots in the book, the dry weight of the roots in the book, the total number of roots, and the total fresh weight of the roots; (2) administration of NAA by immersion is better than dipping in the number of roots in the book, the fresh weight of the roots in the book, the dry weight of the roots in the book, the total number of roots, and the total fresh weight of the roots; and (3) length of soaking cuttings in NAA solution has no effect on the growth of pepper cuttings.